2016
DOI: 10.1155/2016/7108261
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel Intracellular Sucrase Enzyme ofLeishmania donovaniPromastigotes

Abstract: The promastigote stage of Leishmania resides in the sand fly gut, enriched with sugar molecules. Recently we reported that Leishmania donovani possesses a sucrose uptake system and a stable pool of intracellular sucrose metabolizing enzyme. In the present study, we purified the intracellular sucrase nearly to its homogeneity and compared it with the purified extracellular sucrase. The estimated size of intracellular sucrase is ~112 kDa by gel filtration chromatography, native PAGE, and substrate staining. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Treatment with sake yeast supplement improved GSH and TAS levels which may be due to decreased production of free radicals and increased level of antioxidants. Previous studies have reported that STZ causes diabetes by elevating sensitivity to lipid peroxidation and oxidative stress, thus pointing to mechanisms probably involved in the pathogenesis of the disease 9,21. MDA has been reported as one of the products of lipid peroxidation that is rapidly mixed with biomolecules and therefore disturbs the glucose metabolism 22.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with sake yeast supplement improved GSH and TAS levels which may be due to decreased production of free radicals and increased level of antioxidants. Previous studies have reported that STZ causes diabetes by elevating sensitivity to lipid peroxidation and oxidative stress, thus pointing to mechanisms probably involved in the pathogenesis of the disease 9,21. MDA has been reported as one of the products of lipid peroxidation that is rapidly mixed with biomolecules and therefore disturbs the glucose metabolism 22.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia and hypercholesterolemia are known as common signs in diabetes 28. Studies have also reported that STZ increases the sensitivity to lipid peroxidation 9,29. Decreased hepatic insulin sensitivity could be attributed to increased hepatic gluconeogenesis, postprandial hyperinsulinemia, and increased production of triglycerides in the liver cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, significant inhibition by PMSF indicates the presence of the amino acid serine in the catalytic site. The inhibition by the thiol modifying reagent NEM depicts the presence of sulphydryl groups (‐SH) in the active site of β‐ d ‐fructofuranosidase (Singh & Mandal, ). The inhibition by TLCK indicates the possibility of histidine moieties, as well as the inhibition by NBS may indicate the presence of histidine/tryptophan/methionine amino groups in the catalytic triad.…”
Section: Discussionmentioning
confidence: 99%